Xây dựng và sử dụng tiêu chí đánh giá hoạt động học của học sinh trong dạy học môn Khoa học tự nhiên lớp 8, chương trình Cambridge - Nguyễn Thị Hằng Nga, Nguyễn Thị Hằng Nga; Nguyễn Thị Diệu Linh, Nguyễn Thị Diệu Linh (Tạp chí Giáo dục, 2026)
Vietnamese education is shifting from teaching focusing on content and knowledge to teaching to develop students' capacity. Therefore, the assessment also needs to be adjusted accordingly. Process assessment is intended to provide timely feedback on teaching and learning activities and as a means of stimulating student learning. The Natural Science subject of the Cambridge Program is built on the scientific basis of the fields of Physics, Chemistry, Biology, and Earth Science, which is a subject that combines theory with practice. Through learning activities, students can explore the natural world and experience the thinking of scientists. Thereby, their abilities are revealed and developed. However, the assessment of student's abilities is a challenge for many teachers. This research proposes principles and procedures for developing criteria for evaluating student learning activities, and procedures for using these criteria to meet the teaching objectives of developing qualities and competencies.